Answer:
ill answer in a bit
Step-by-step explanation:
Answer:
- 5/7 - (3/14 + 3/14) = 2/7
See the steps of solution:
- 5/7 - (3/14 + 3/14) = Solve parenthesis first
- 5/7 - (3 + 3)/14 = Add fractions with same denominator
- 5/7 - 6/14 = Simplify
- 5/7 - 3/7 = Subtract fractions with same denominator
- (5 - 3)/7 = Simplify
- 2/7 Answer
This image is not loading therefore no one can answer it
Answer: <em>10 + 9 </em>
Step-by-step explanation:
<em>1. Distribute: 3(6+3) - (8-x) = 18 + 9 - (8)</em>
<em>2. Eliminate redundant parentheses: 18 + 9 - (8) = 18 + 9 - 1 ⋅ 8</em>
<em>3. Multiply the numbers: 18 + 9 - 1 ⋅ 8 = 18 + 9 - 8 </em>
4. Combine like terms: 18 + 9 - 8 = 10 + 9
<em>⋅</em>
<em />